PENGARUH PROFITABILITAS DAN BIAYA OPERASIONAL TERHADAP PAJAK PENGHASILAN BADAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI SUB-SEKTOR FARMASI PADA TAHUN 2015-2019 - Andres Hiltown Naibaho; Lorina Siregar Sudjiman (Jurnal Ekonomis, 2021)
Corporate income tax is an obligation given to company for its income then deposited into the state treasury. However, this tax is an obligation that is not liked by many parties. Therefore, the author makes this study aims to see how the influence of profitability and operating costs on corporate income tax in manufacturing companies listed on the IDX of the pharmaceutical Sub-Sector in 2015-2019. This study uses purposive sampling technique as many as 8 companies with company codes, namely: DVLA, INAF, KAEF, KLBF, MERK, PYFA, SIDO, TSPC, the number of sampling is 40 research data. This type of research is quantitative research that uses the annual financial statements of manufacturing companies listed on the IDX for the Pharmaceutical Sub-Sector in 2015-2019. In this study the authors used coefficient of determination, descriptive statistical tests, autocorrelation test, data normality test, heteroscedasticity, multicollinearity test, T significant test, and F significant test. This results of this research are; 1) profitability has a partial effect on corporate income tax, 2) operating costs have no significant effect on corporate income tax, and 3) profitability and operating costs have a simultaneously effect on corporate income tax in manufacturing companies listed on the Indonesia Stock Exchange for the Pharmaceutical Sub-Sector in 2015- 2019.